2020
DOI: 10.1007/jhep04(2020)190
|View full text |Cite
|
Sign up to set email alerts
|

Chiral decoupling from irrelevant deformations

Abstract: We show that in the limit in which the TT deformation parameter is sent to infinity, the left-and right-chiral sectors of TT-deformed free theories decouple.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…With the fully resummed TT-deformed Lagrangian in eq. ( 4.28), it is only natural to ask, following our earlier investigations [21], what happens to this theory in the limit of infinite coupling. In our earlier work, it was important that we work in the Hamiltonian formalism -this was the only way to sensibly take this limit.…”
Section: Infinite Coupling Limitmentioning
confidence: 89%
See 2 more Smart Citations
“…With the fully resummed TT-deformed Lagrangian in eq. ( 4.28), it is only natural to ask, following our earlier investigations [21], what happens to this theory in the limit of infinite coupling. In our earlier work, it was important that we work in the Hamiltonian formalism -this was the only way to sensibly take this limit.…”
Section: Infinite Coupling Limitmentioning
confidence: 89%
“…Clearly, this term is purely topological and naturally does not contribute to the stress tensor. This line of investigation might be able to explain a puzzle we raised in [21]: how is it possible for strongly interacting chiral fermions to, in the infinite coupling limit, decouple? Once we take the infinite coupling limit such that S ± is held fixed, we see that the topological term becomes insignificant, leaving us once again with the free fermion Lagrangian.…”
Section: Jhep02(2021)028mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the results obtained from the Hamiltonian formalism are reproduced in the Lagrangian path integral formalism, in general, due to the emergence of higher derivative terms in the deformed Lagrangian (3.4), (3.6), the equivalence between the Lagrangian path integral formalism and the Hamiltonian path integral formalism remains as a mystery. For instance, though Legendre transformation, it can be found that the Minkowski Hamiltonian of the deformed free bosons takes the form [43,54] H…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A possible interpretation of this picture is the following: in this ultra-relativistic limit the string becomes chiral in the subsector where it is moving one way around the longitudinal spatial circle and antichiral in the subsector where it is moving the other way around this direction. For a single transverse scalar, the above limit was considered in [43] and used to provide a description of a chiral boson starting with the gauge fixed Nambu-Goto action; in [44] this was reinterpreted in the TT context and the presence of chiral and antichiral sectors also suggested.…”
Section: From Non-relativistic To Ultra-relativisticmentioning
confidence: 99%